2014
DOI: 10.1002/lt.23829
|View full text |Cite
|
Sign up to set email alerts
|

National assessment of early biliary complications following liver transplantation: Incidence and outcomes

Abstract: Despite improved overall liver transplant outcomes, biliary complications remain a significant cause of morbidity. A national data set linking transplant registry and Medicare claims data for 17,012 liver transplant recipients was used to identify all recipients with a posttransplant biliary diagnosis code within the first 6 months after transplantation. Patients were further categorized as follows: a diagnosis without a procedure, a diagnosis and an associated radiological or endoscopic procedure, or a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 24 publications
6
58
2
2
Order By: Relevance
“…While the use of health care claims limits the detailed analysis of care processes, these methods clearly identify patients with clinically significant biliary issues. Prior analyses using these methods, demonstrated that patients identified using a combination of diagnostic and procedure codes had over twice the rate of death and graft failure when compared with patients without BCs (21). These findings remain robust after adjustment for donor and recipient characteristics, as well as in stratified analysis considering DCD and DBD transplant separately.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…While the use of health care claims limits the detailed analysis of care processes, these methods clearly identify patients with clinically significant biliary issues. Prior analyses using these methods, demonstrated that patients identified using a combination of diagnostic and procedure codes had over twice the rate of death and graft failure when compared with patients without BCs (21). These findings remain robust after adjustment for donor and recipient characteristics, as well as in stratified analysis considering DCD and DBD transplant separately.…”
Section: Discussionmentioning
confidence: 97%
“…In transplantation, this equation is made even more complex as a result of the substantial differences in donor quality and transplant factors such as cold ischemic times and choice of preservation solution (11,(15)(16)(17)(18)(19)21,25). In previous analyses, recipient factors including increased patient age, female gender, preoperative hyperbilirubinemia, retransplantation, smoking status, and socioeconomic status have all been found to increase the rate of a biliary leak, stricture or both.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations